Ultrastructural detection of proteins, lipids and carbohydrates in oocytes of Amblyomma triste (Koch, 1844) (Acari; Ixodidae) during the vitellogenesis process - Ricardo, Amanda Juliana; de Oliveira, Patricia Rosa; Bechara, Gervasio Henrique; Camargo Mathias, Maria Izabel (Churchill Livingstone, 2007)
The ovary of the tick Ainblyomma triste is classified as panoistic, which is characterized by the presence of oogonia without nurse and follicular cells. The present study has demonstrated that the oocytes in all developmental stages (I-IV) are attached to the ovary through a pedicel, a cellular structure that synthesizes and provides carbohydrate, lipids and proteins supplies for the oocytes during the vitellogenesis process. The lipids are deposited during all oocyte stages; they are freely distributed as observed in stages II, III and IV or they form complexes with other elements. The proteins are also deposited in all stages of the oocytes, however, in lower concentration in the stage IV. There is carbohydrate deposition from oocytes in the stage II as well as in stages III and IV. In addition, the present work has demonstrated that the oocyte yolk of A. triste has a glycolipoprotein nature and the elements are deposited in the following sequence: firstly the lipids and proteins, and finally the carbohydrates. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: tick; ovary; cytochemistry; lipids; Proteins; Carbohydrates